Respuesta :
The answer is a.)(x - 4)2 = 3.
(x - a)² = b can be expressed as:
x² - 2ax + a² = b ⇒ x² - 2ax + a² - b = 0
Our equation is x² - 8x + 13 = 0.
The general formula is x² - 2ax + (a² - b) = 0
Thus:
8x = 2ax and a² - b = 13
Divide both sides of the first equation (8x = 2ax) by x:
8 = 2a ⇒ a = 8 ÷ 2 = 4
Replace a in the second equation (a² - b = 13):
4² - b = 13 ⇒ b = 4² - 13 = 16 - 13 = 3
Now when we have a and b, let's just replace them in the general equation:
(x - a)² = b
(x - 4)² = 3
(x - a)² = b can be expressed as:
x² - 2ax + a² = b ⇒ x² - 2ax + a² - b = 0
Our equation is x² - 8x + 13 = 0.
The general formula is x² - 2ax + (a² - b) = 0
Thus:
8x = 2ax and a² - b = 13
Divide both sides of the first equation (8x = 2ax) by x:
8 = 2a ⇒ a = 8 ÷ 2 = 4
Replace a in the second equation (a² - b = 13):
4² - b = 13 ⇒ b = 4² - 13 = 16 - 13 = 3
Now when we have a and b, let's just replace them in the general equation:
(x - a)² = b
(x - 4)² = 3
Answer:
a=4 and b=3
Step-by-step explanation:
Just took the test, and got it correct